2021
DOI: 10.1111/jfpp.15524
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical qualities and antioxidant properties of juice extracted from ripe and overripe wax apple as affected by pasteurization and sonication

Abstract: The present study investigated the effect of sonication alone and sonication with subsequent pasteurization on physicochemical and antioxidant properties of juice extracted from the ripe or overripe wax apple. Samples were sonicated for varying times (0–10 min) at a fixed frequency (28 kHz) and temperature (20°C) and then, pasteurized at 90°C for 2 min. Irrespective of the maturity, sonication improved the color characteristics (lightness, chroma, and hue) of wax apple juices (p > .05). Other quality parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 44 publications
3
13
0
Order By: Relevance
“…Sonication effectiveness relies upon multiple intrinsic and extrinsic processing conditions [68] . Earlier, Tiwari et al [72] reported a significant reduction in PME activity in orange juice and Bavisetty and Venkatachalam [73] in PG activity in apple juice through sonication processing.…”
Section: Resultsmentioning
confidence: 96%
“…Sonication effectiveness relies upon multiple intrinsic and extrinsic processing conditions [68] . Earlier, Tiwari et al [72] reported a significant reduction in PME activity in orange juice and Bavisetty and Venkatachalam [73] in PG activity in apple juice through sonication processing.…”
Section: Resultsmentioning
confidence: 96%
“…Moreover, ingesting apples can reduce the risk of diseases and prevent chronic diseases, cancer and cardiovascular diseases due to the bioactive compounds in apples ( 5 ). However, the industrial processing of apple juice, such as pasteurization, steaming, and chemical preservatives, is causing undesirable physical, chemical and nutritional changes to the products ( 6 ). Fermented apple juice (FAJ) by LAB is one of the most effective and convenient methods to improve this situation.…”
Section: Introductionmentioning
confidence: 99%
“…Bavisetty and Venkatachalam [20] also reported, the reduction of TSS in wax apple juice samples sonicated with subsequent pasteurization was greater than with sonication alone. All juices showed parallel titratable acidity (TA) changes when processed, independent of maturity (Figure 2(c)).…”
Section: Effects Of Treatments On Ph Total Soluble Solids (Tsss) and ...mentioning
confidence: 89%
“…Venkatachalam [20] with slight modification. For pasteurization process, juices were transported into sterilized glass jars (400 ± 2 ml).…”
Section: Experimental Designmentioning
confidence: 99%